Unusual Etiology and Diagnosis of Oroantral Communication due to Late Implant Failure - Rabah Nedir; Nathalie Nurdin; Marion Paris; Marc El Hage; Semaan Abi Najm; Mark Bischof (Case Reports in Dentistry)
Oroantral communication (OAC) rarely occurs long after implant placement. The present report describes the rare etiology and the difficulty of the diagnosis of an uncommon OAC occurring 10 years after the implant placement in the posterior maxilla. The difficulty of the diagnosis lies in the absence of clinical symptoms of sinusitis and presence of multiunit prosthesis hiding implant failure. This case report supports the need for sinus check-up during a routine implant examination.